1.
\(\Leftrightarrow2x\left(2x+3\right)-\left(2x+3\right)=0\)
\(\Leftrightarrow\left(2x-1\right)\left(2x+3\right)=0\)
\(\Rightarrow\left\{{}\begin{matrix}x=\dfrac{1}{2}\\x=-\dfrac{3}{2}\end{matrix}\right.\)
2.
\(\Leftrightarrow-3x^2+9x=0\)
\(\Leftrightarrow-x\left(3x-9\right)=0\)
\(\Rightarrow\left\{{}\begin{matrix}x=0\\x=3\end{matrix}\right.\)
1) \(2x\left(2x+3\right)-2x-3=0\)
\(\Rightarrow\left(2x-1\right)\left(2x+3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}2x-1=0\\2x+3=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=-\dfrac{3}{2}\end{matrix}\right.\)
2) \(3x^2-6x^2+9x=0\)
\(\Rightarrow-3x^2+9x=0\)
\(\Rightarrow-3x\left(x-3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}-3x=0\\x-3=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=3\end{matrix}\right.\)